Field notes contributed by John Van Dyk, winter 1978-1979 - Van Dyk, Johnet al (1978)
Winter report of birds found in northwest Iowa contributed by John Van Dyk. Weather conditions were reported as being extremely cold and snowy for this time period. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1978-1979. Epson - sheet feed/flatbed